Viscoelastic power law parameters of in vivo human brain estimated by MR elastography - Testu, J.; Mcgarry, M. D. J.; Dittmann, F.; Weaver, J. B.; Paulsen, K. D.; Van Houten, E. E. W.; Sack, Ingolf (Journal of the Mechanical Behavior of Biomedical Materials, 2017)
The noninvasive imaging technique of magnetic resonance elastography (MRE) was used to estimate the power law behavior of the viscoelastic properties of the human brain in vivo. The mechanical properties for four volunteers are investigated using shear waves induced over a frequency range of 10–50 Hz to produce a displacement field measured by magnetic resonance motion-encoding gradients. The average storage modulus (μR) reconstructed with non-linear inversion (NLI) increased from approximately 0.95 to 2.58 kPa over the 10–50 Hz span; the average loss modulus (μI) also increased from 0.29 to 1.25 kPa over the range. These increases were modeled by independent power law (PL) relations for μR and μI returning whole brain, group mean exponent values of 0.88 and 1.07 respectively. Investigation of these exponents also showed distinctly different behavior in the region of the cerebral falx compared to other brain structures.
CRIS-Team Scopus Importer:2022-08-03
Keywords: Elastography; MRE; Power law; Viscoelastic